Consumption habits and economic impact of Liebherr 2019 ITTF World Table Tennis Championships - Tamás Laczkó; Pongrác Ács; Miklós Stocker; Dávid Paár (Universidad de Granada, 2020)
Organising international sports events became one of the most important elements of the prioritized sports sector in Hungary. The main goal of this study was to examine the economic impact of Liebherr 2019 ITTF World Table Tennis Championships (WTTC) for the Hungarian GDP. The impact is based on consumption habits of stakeholders and total budget of organisers so it was necessary to analyse the characteristics of passive sports tourists and all other stakeholders and their spending too. Consumption of stakeholders were surveyed with questionnaire (n=1097) and the budget of the organisers were presented by the Hungarian Table Tennis Association. We have used the secondary data of Hungarian Statistical Office and Eurostat for input-output modelling. Expenditures and spending behaviour of stakeholders were calculated by inferential statistics, differences were tested by independent-samples T tests, ANOVA and Chi-square tests. Input-output modelling method was used for estimating the direct and indirect macroeconomic impacts. Daily spending of domestic (47.9 EUR/day) and foreign (102.8 EUR/day) passive sports tourists coming to the WTTC were calculated. Foreign passive sports tourists spent an average 3.85 days in the country. Examining the macroeconomic effects it can be stated that every EUR of government support increased the country's GDP by 1.21 EUR and generated a tax of 1.01 EUR in 2019. Expenditures of spectators and participants contributed 24% of the generated GDP. Passive sports tourists of WTTC spent more money than the general domestic and foreign tourists (20.6 EUR/day and 51.8 EUR/day respectively) or even the domestic or foreign sports tourists (24.7 EUR/day and 54.7 EUR/day respectively). They spent more time than general foreign tourists or foreign sports tourists as well (2.26 days and 2.29 days respectively) in Hungary. The Hungarian government provided almost 4 million euros support to the organisers and this amount is exceeded by the total contribution of WTTC to the Hungarian GDP (4.7 million EUR).